Availability and affordability of medicines and cardiovascular outcomes in 21 high-income, middle-income and low-income countries - Annika Rosengren; Khalid Yusoff; Karen E Yeates; Wei Li; Rajeev Gupta; Koon Teo; Sumathy Rangarajan; Scott A Lear; Rasha Khatib; Rafael Diaz; Alvaro Avezum; Fernando Lanas; et al. (BMJ Global Health)
Objectives We aimed to examine the relationship between access to medicine for cardiovascular disease (CVD) and major adverse cardiovascular events (MACEs) among people at high risk of CVD in high-income countries (HICs), upper and lower middle-income countries (UMICs, LMICs) and low-income countries (LICs) participating in the Prospective Urban Rural Epidemiology (PURE) study.Methods We defined high CVD risk as the presence of any of the following: hypertension, coronary artery disease, stroke, smoker, diabetes or age >55 years. Availability and affordability of blood pressure lowering drugs, antiplatelets and statins were obtained from pharmacies. Participants were categorised: group 1—all three drug types were available and affordable, group 2—all three drugs were available but not affordable and group 3—all three drugs were not available. We used multivariable Cox proportional hazard models with nested clustering at country and community levels, adjusting for comorbidities, sociodemographic and economic factors.Results Of 163 466 participants, there were 93 200 with high CVD risk from 21 countries (mean age 54.7, 49% female). Of these, 44.9% were from group 1, 29.4% from group 2 and 25.7% from group 3. Compared with participants from group 1, the risk of MACEs was higher among participants in group 2 (HR 1.19, 95% CI 1.07 to 1.31), and among participants from group 3 (HR 1.25, 95% CI 1.08 to 1.50).Conclusion Lower availability and affordability of essential CVD medicines were associated with higher risk of MACEs and mortality. Improving access to CVD medicines should be a key part of the strategy to lower CVD globally.